Sustainable techniques for thermal comfort in buildings designed used by worshipers - Alabdullatief, Aasem; Omer, Siddig (2017)
Thermal comfort in building is a trendy that has been under investigation by many researchers. The mosque, for Muslim worshippers, is one of the most popular religious buildings. The demand of new mosques is continuously increasing due to the increasing number of Muslims population and growth in both economic and urban land escape. Recently, there have been a reasonable number of researches that have been investigating the thermal performance of mosque buildings. As a matter of fact, the location of the mosque and the climate play key roles on mosque building thermal performance. Additionally, mosque buildings are unique because of the intermittent operation pattern and the varying number of the users, which require rather controlled heating or cooling strategies. Sustainable energy techniques are keystone that ensures low energy consumption and provide better indoor environment for users of buildings. On the other hand due to environmental pressure to suppress global warming, more energy efficient and sustainable buildings design is one of the current issues in building industries. This research explores application of sustainable technologies for mosque buildings in hot climate zone. A number of mosque buildings in different regions, time frame and climates have been studied, and application of passive techniques on these cases have been evaluated. Performance of these techniques on roofs including building insulation, shading and green roofing have been analysed taking into account the climate and building specifications. The preliminary results obtained from this research clearly indicate that, there are design correlations and guidelines to be established for the architects and mosque buildings designers under any given climate for a sustainable mosque building design. Use of these guidelines also have potential of financial saving appropriately applied in mosque buildings in hot arid climate.